2008
DOI: 10.1055/s-2008-1077296
|View full text |Cite
|
Sign up to set email alerts
|

In vivo confocal laser endomicroscopy of the human liver: a novel method for assessing liver microarchitecture in real time

Abstract: A miniaturized imaging system for confocal laparoscopy allowed in vivo microscopic analysis of healthy and diseased human liver for the first time during ongoing minilaparoscopy. Although such in vivo imaging does not yet compete with conventional histopathology, this novel confocal laparoscopy system may be of future relevance for immediate morphodynamic analysis in liver disease and the targeting of biopsies in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 19 publications
0
42
0
1
Order By: Relevance
“…Thus, there is a desperate need for a rapid, accurate and safe histological diagnosis method for the successful diagnosis and management of liver disease. Goetz et al has recently reported the application of confocal laser endomicroscopy for the real-time histological examination of liver disease in both animal models and human [7,8]. This technology allows immediate in vivo subsurface microscopic imaging and has potential to dynamically monitor pathologic events of liver with high resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a desperate need for a rapid, accurate and safe histological diagnosis method for the successful diagnosis and management of liver disease. Goetz et al has recently reported the application of confocal laser endomicroscopy for the real-time histological examination of liver disease in both animal models and human [7,8]. This technology allows immediate in vivo subsurface microscopic imaging and has potential to dynamically monitor pathologic events of liver with high resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Noninvasive biomedical imaging techniques such as ultrasonography, computed tomography, and magnetic resonance imaging are widely used to detect liver disease, but they do not have sufficient sensitivity, spatial resolution, or specificity to detect or stage liver disease (Lin et al, 2012). By contrast, virtual biopsies obtained via fluorescence imaging can give an overall view of the liver (Goetz et al, 2008a) as well as provide dynamic information (Goetz et al, 2008b). The latter technique remains useful regardless of sample preparation (e.g., frozen or paraffin-embedded tissue), is easy and fast, has no sampling bias (Gailhouste et al, 2010), and may potentially quantify liver diseases such as fibrosis (He et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescein has been used to study liver function in humans, permitting visualization of hepatocytes, bile ducts, sinusoids, and collagen fibers in vivo (Goetz et al, 2008a). Fluorescein, which rapidly diffuses throughout the body in seconds, is taken up by the hepatocytes, metabolized to fluorescein monoglucuronide (FG), and excreted into the bile by active transport (Sherman and Fisher, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…35 Finally, a recent case report used pCLE to detect villous structures of intraductal papillary mucinous tumors of the pancreas. 36 …”
Section: Hepatobiliary/pancreasmentioning
confidence: 99%